(untitled) (The South East European Journal of Economics and Business, 2025)
This paper aims to evaluate the foreign direct investment in North Macedonia, a small developing economy. Findings indicate that after the dissolution of Yugoslavia, North Macedonia’s policy of economic openness was generally successful and the country attracted substantial amounts of FDI by using its Technological industrial development zones and leveraging proximity to EU markets. By applying the gravity model to a panel of data, spanning 35 countries and a period of 14 years (2010-2023), this paper argues that economic dimensions of the host and source countries, geographic proximity, relative economic distance, economic integration, historical and cultural proximity, bilateral investment treaties and double taxation avoidance agreements have a positive impact on FDI. However, this paper does not find conclusive evidence that inflation rates, political corruption and innovation influence the FDI stock. In light of the need to avoid high concentration in just a few economic segments and high dependence on several source countries, the paper points out the need to simultaneously attract and diversify sources of foreign capital in order to enhance resilience to exogenous shocks. Diversified FDI stock is pivotal for achieving long-term macroeconomic stability and maintaining higher growth rates.